Denmark : Detailed Assessment of Observance of the Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses findings of the Detailed Assessment of Observance of the Insurance Core Principles on Denmark. Insurance regulation in Denmark has a good level of compliance with the Insurance Core Principles. A particular strength of the Danish Financial Supervisory Authority's approach is its close focus on key risks in the sector and its readiness to require action by companies to address vulnerabilities. Regular, even daily monitoring of market risk sensitivities is carried out on life insurers' balance sheets. In nonlife insurance, regular testing of a number of key performance ratios helps to highlight potential weaknesses and to support early intervention. There is comprehensive oversight of the reinsurance programs of the nonlife companies in particular.